Optimalisasi Drone Dan GIS Untuk Pemetaan Wilayah Dan Penegasan Alamat Di Kelurahan Pasir Panjang, Kota Kupang: Optimization Of Drones And GIS For Area Mapping And Address Affirmation In Pasir Panjang Village, Kupang City - Hayer, Yacob Victor; Nama, Arnoldus; Jawal Nope, Fabi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The development of drone technology and Geographic Information Systems (GIS) has provided new opportunities in mapping and address verification. This study aims to optimize the use of drones and GIS for regional mapping and address confirmation in Pasir Panjang, Kupang City. The methodology includes collecting spatial and attribute data, processing aerial imagery using photogrammetric software, and creating geospatial maps with attribute information. The study identifies key challenges such as the lack of standardized address naming, unnumbered buildings, and unclear administrative boundaries. The results highlight the effectiveness of drone-integrated GIS in producing accurate and up-to-date geospatial data, supporting urban planning and public services. This research also provides recommendations for policy improvements in address standardization and urban management in Kupang City.